MVC Implementation In Laravel Framework For Development Web-Based E-Commerce Applications - Gatot Budi Santoso; Tondi Mulia Sinaga; Ahmad Zuhdi (Penerbitan Universitas Trisakti, 2021)
MVC is a concept that separates three main logical components namely model, view and controller. The model represents the database, the view controls the user interface and controller connecting the model and view. The MVC concept makes coding work more structured. Laravel is a PHP framework that uses the concept of MVC so that the use of Laravel to develop an application greatly facilitates the programmer. Besides other facilities offered by Laravel, Laravel provides lightweight layout templates, provides a lot of object oriented libraries and has artistic tools for carrying out commands at the command line that can help programmers build a website or web-based application. With the many conveniences offered by Laravel, the process of developing a large website becomes easier and faster. In this research the development of web-based e-commerce applications is made using the Laravel framework.